2004
DOI: 10.1038/nsmb794
|View full text |Cite
|
Sign up to set email alerts
|

Closed state of both binding domains of homodimeric mGlu receptors is required for full activity

Abstract: Membrane receptors, key components in signal transduction, often function as dimers. These include some G protein-coupled receptors such as metabotropic glutamate (mGlu) receptors that have large extracellular domains (ECDs) where agonists bind. How agonist binding in dimeric ECDs activates the effector domains remains largely unknown. The structure of the dimeric ECDs of mGlu(1) solved in the presence of agonist revealed two specific conformations in which either one or both protomers are in an agonist-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
197
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 254 publications
(224 citation statements)
references
References 42 publications
25
197
2
Order By: Relevance
“…Using chimerical GABAb receptor subunits bearing the carboxyl-termini of mGluR1a and mGluR1b splice variants resulted in four GB/mGluR subunits (GB1 or GB2 subunits with either mGluR1a or mGluR1b C-termini). In our previous studies we used chimerical receptors with reverse strategy Kniazeff et al, 2004). In these we introduced C-termini of GB1 and GB2 subunits into mGlu receptor subunits with the aim to direct their heterodimerization taking advantage of the dimerization quality-control machinery encoded in those regions.…”
Section: Discussionmentioning
confidence: 99%
“…Using chimerical GABAb receptor subunits bearing the carboxyl-termini of mGluR1a and mGluR1b splice variants resulted in four GB/mGluR subunits (GB1 or GB2 subunits with either mGluR1a or mGluR1b C-termini). In our previous studies we used chimerical receptors with reverse strategy Kniazeff et al, 2004). In these we introduced C-termini of GB1 and GB2 subunits into mGlu receptor subunits with the aim to direct their heterodimerization taking advantage of the dimerization quality-control machinery encoded in those regions.…”
Section: Discussionmentioning
confidence: 99%
“…Initial structural studies of the isolated ECD dimer revealed that agonist binding in the orthosteric-binding site stabilizes an active (A) state, where the two ECDs are reoriented by 70°, compared with the resting (R) state obtained in the presence of an antagonist (Fig. 1b) [17][18][19] . Yet, other crystal structures have, surprisingly, revealed that the ECD dimer can also adopt either a resting orientation with a bound agonist 16 , or an active orientation in the presence of antagonists, which raises a number of questions regarding the real activation mechanism of these receptors and the mechanism of partial agonism (Fig.…”
mentioning
confidence: 99%
“…In the absence of ligand or in the presence of antagonists, both VFTs are opened (oo). The binding of one or two agonists triggers the closure of one (co) or two VFTs (cc) in the dimer, resulting in receptor activation (13).…”
mentioning
confidence: 99%
“…The ECD is composed of a Venus flytrap (VFT) bilobate domain containing the agonist binding site (12)(13)(14)(15) and a cysteine-rich domain (CRD) that connects the VFT to the TMD (16). The VFTs exist in two major states: an open state (o) in absence of ligand and stabilized by antagonists, and a closed state (c) stabilized by agonists and required for receptor activation (12)(13)(14)(15). The VFT dimer is in equilibrium between various conformations, depending on whether one or two VFTs are open or closed.…”
mentioning
confidence: 99%